The key role of protection status in safeguarding the ecological functions of some Neotropical mammals - Nagy-Reis, Mariana B.; Ribeiro, Milton Cezar [UNESP]; Setz, Eleonore Z. F.; Chiarello, Adriano G. (Springer Nature, 2019)
Protected areas can mediate negative effects of habitat loss and human-related pressures on key ecological groups. However, different protected area categories can vary substantially in their degree of enforcement, which may ensure different levels of effectiveness for biodiversity protection. Because little attempt has been made to quantify this, we investigated the protection effectiveness of different levels of protection (low, intermediate, and high) in maintaining the ecological functions of mammalian species. We assessed this on a selection of five species with varying ecological functions: nine-banded armadillo (insectivore), paca (seed disperser), tayra (omnivore), ocelot (carnivore), and collared peccary (seed predator). Their occupancy probability and the integrity of their ecological functions were estimated and spatialized across landscapes at all protection levels (low, intermediate, and high). In addition, we estimated how many of these species were maintained in each protection status using a minimum of 35% occupancy threshold for each. Our results indicated that higher protection statuses can hold more ecological functions of these mammalian species than areas with lower protection levels. Ocelot and paca heavily relied on areas with higher protection, which can impact the overall ecosystem functioning and ecological services of less protected areas, since these are species performing unique roles in our landscape (mixed-sized prey carnivory and large-sized seed dispersal, respectively). Our study suggests that the degrees of protection can influence the area effectiveness in maintaining certain mammalian species and their ecological functions and ecosystem services. Therefore, management strategies and degree of enforcement should be carefully planned when assigning areas for conservation to ensure the conservation of more sensitive species and preserve more ecological functions.
Keywords: Carnivory; Ecosystem services; Mammal conservation; Protected areas; Seed dispersal